PERBEDAAN MASAKAN DENGAN TEKNIK MENUMIS DI TIONGKOK DAN TEKNIK MENUMIS DI INDONESIA - Mutiara Prabandari Krisiaputri; Nasya Noor Alyza; Anastasia Siska Wijaya (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
The technique of stir-frying is very popular in Indonesia. Various Indonesian dishes are influenced by various countries around the world, especially China. The influence of Chinese culture and history is very significant in Indonesia, especially in terms of cuisine. With the development of Chinese culture in Indonesia, Indonesians began to learn Chinese cooking techniques, one of which is stir-frying. We would like to discuss the differences between stir-frying techniques in China and Indonesia and how local culture influences these techniques. The research method we used was literature analysis, searching for information from various reliable sources. The Chinese stir-frying technique is cooked quickly, while the Indonesian cooking technique is cooked for a longer time. There are quite a few differences, starting from the process, spices, the results of the cooking, and the taste of the dish, which are the characteristics of the dish itself. The cultural differences between China and Indonesia have resulted in the adaptation of dishes, producing a variety of dishes.